Student's perception of the use of Spotify song feature to improve English listening skill - Rahmadewi, Dea Putri; Ummi Nur Laila Sulistyani (ELT Forum: Journal of English Language Teaching, 2025)
The development of the Digital Era has significantly changed education, especially in terms of language learning. Digital learning, like Spotify, is becoming more important. Even with the growing popularity of digital media, few people know about how learners’ perception of Spotify’s song features in terms of improving their listening knowledge in English. By doing a systematic literature review and combining knowledge from every article that has the same topics like as “music streaming”, “English language learners”, “EFL”, “listening skills”, “Spotify”, “listening comprehension”, “EFL”, and “ESL” from 2018-2025 article, this article fills this knowledge gap from each article. According to the main conclusion, Spotify gives language learners with couple of important advantages. It offers information that Spotify is easy to access, can greatly increase learners' interest and participation, and supports the growth of vocabulary, pronunciation, and listening skills. Overall, there is a good opinion of Spotify as an educational tool. It’s important to recognize some of the difficulties, such as digital differences between learners, distraction, and over-reliance on the lyrics. The relevance of this research originates from its full investigation of learners’ crucial perspectives on Spotify music and it can be fact-based advice for language teachers on how to apply digital resources like Spotify while avoiding any negative impact. Additionally, it gives learners ability to make a better decision regarding their English listening practice.